1997
DOI: 10.1093/gerona/52a.1.m1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Immune Function by Dehydroepiandrosterone (DHEA) in Age-Advanced Men

Abstract: Background. Substantial data from animal studies have demonstrated a stimulatory effect of dehydroepiandrosterone (DHEA) on immune function. However, little is known about the effects of DHEA on the human immune system. Since aging is associated with a decline in immune function and in DHEA production, we proposed that oral administration of DHEA to elderly men would result in activation of their immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
2
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(90 citation statements)
references
References 41 publications
(36 reference statements)
2
84
2
2
Order By: Relevance
“…When aged individuals, being it experimental animals (36±38) or humans (39) are administered DHEA, their immune function has been claimed to be restored; they become more resistant to infections, their secretion of T cell cytokines (e.g. IL-2) is enhanced, whereas monocyte numbers are increased.…”
Section: Discussionmentioning
confidence: 99%
“…When aged individuals, being it experimental animals (36±38) or humans (39) are administered DHEA, their immune function has been claimed to be restored; they become more resistant to infections, their secretion of T cell cytokines (e.g. IL-2) is enhanced, whereas monocyte numbers are increased.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dehydroepiandrosterone sulfate (DHEAS) has been proposed for the treatment of systemic lupus erythematosus (33). It is well known that DHEAS exerts multiple immune functions (34,35) also enhancing NKCC via local production of the immunoregulatory peptide insulin-like growth factor I (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, testosterone levels are markedly raised in women taking DHEA as a dietary supplement (Morales et al, 1994(Morales et al, , 1998Khorram et al, 1997;Casson et al, 1998). International studies report that Chinese women show lower mean testosterone concentrations than do Western women and also have a very much lower incidence of breast cancer (Key et al, 1990).…”
Section: Possible Role For Dhea In Mammary Carcinogenesismentioning
confidence: 99%
“…Serum concentrations of insulin-like growth factor 1 (IGF1) were elevated and sex hormone-binding globulin levels in the circulation were reduced in both sexes. Immune activity was activated both in men (Khorram et al, 1997) and women (Morales et al, 1998) while total body mass was increased in women but fat mass decreased in men. The increased IGF1 levels were similar for 50 mg DHEA daily for 3 months to those for 100 mg daily for 6 months (Morales et al, 1998) but no change was found in insulin concentrations.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation